Efficacy of nitrofuran derivatives against biofilms of Histoplasma capsulatum strains and their in vivo toxicity - Vaso, Carolina Orlando [UNESP]; Bila, Níura Madalena [UNESP]; da Silva, Rosângela Aparecida Moraes [UNESP]; de Carvalho, Angélica Romão [UNESP]; Belizário, Jennyfie Araújo [UNESP]; Pandolfi, Fabiana; De Vita, Daniela; Bortolami, Martina; Mendes-Giannini, Maria José Soares [UNESP]; Scipione, Luigi; Di Santo, Roberto; Costi, Roberta; et al. (Taylor & Francis, 2025)
Aim: To evaluate the efficacy of two nitrofuran derivatives against biofilms formed by two strains of Histoplasma capsulatum and to study the toxicity of these compounds in alternative models: Caenorhabditis elegans, Galleria mellonella, and zebrafish. Methods: The metabolic activity of biofilms was measured after treatment using the XTT reduction assay. Scanning electron microscopy (SEM) and confocal microscopy were used to observe damage to mature biofilms. Survival curves were generated for G. mellonella, while percentage survival was determined for C. elegans and zebrafish. Results: The compounds showed efficacy against early and mature biofilms at concentrations equal to or up to two times higher than those required to eliminate planktonic fungal cells (3.90 to 31.25 μg/mL). Micrographs showed a reduction in metabolic activity, biofilm thickness, and extracellular matrix. In addition, the compounds showed little or no toxicity in alternative models, even at the highest concentrations tested. Conclusion: These results are promising for the development of new therapeutic alternatives, especially for species, such as H. capsulatum, which are recognized as high-priority pathogens. Few studies have investigated resistance and antifungal treatment targeting biofilms of this species, making this work a relevant contribution to future approaches.
Keywords: alternative animals; Antifungal activity; biofilm; Caenorhabditis elegans; Galleria mellonella; nitrofurans; toxicity; zebrafish